The integrated environment selection and prototype сreation of thermal monitoring software - Маргасов, Дмитро Валерійович; Сахно, Євген Юрійович (Technology audit and production reserves, 2015)
The components of information technology in the technological and technical auditing and monitoring of municipal buildings are investigated. The integrated environment is chosen and software prototype of subsystems of thermal monitoring software is created. The subsystem is aimed at the analysis and processing of heterogeneous data on energy efficiency of municipal property and performs decision support and cost calculations of energy-saving measures. The study was carried out as follows: 1. The selected programming language is Java. 2. The selected development environment is NetBeans. NetBeans IDE is integrated development environment written in Java. NetBeans program can run on platforms Windows, Linux, Mac OS and other platforms that support Java virtual machine (JVM), supports the development of programming languages Java, C/C++, PHP, JavaScript and others. 3. The prototype of subsystems of thermal monitoring software is developed and described. These researches may help management of housing and communal services, economics and financial management of city councils to analyze and make ODA decisions to initiate energy saving projects.